2021
DOI: 10.3389/fpsyg.2021.699833
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship for People With Disabilities: From Skills to Social Value

Abstract: Entrepreneurship has undoubted social value as it contributes to socio-economic development of the context where entrepreneurship takes place. When the entrepreneurial activity is undertaken among especially vulnerable groups in the labor market, the multiplying effect of this value is made explicit in society, in general, and in the collective of people with disabilities (PWDs), in particular. The objective of this research study is to explore under which conditions this happens through the analysis not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…This is another area that requires further research. On the other hand, Ortiz García and Olaz Capitán (2021) pointed out that many people with disabilities think that starting up a business may be positively linked to their desire to not receive any more financial benefits from the government. In fact, many of their study participants indicated their desire to start their businesses in order to minimize their need for financial support from the government.…”
Section: Discussionmentioning
confidence: 99%
“…This is another area that requires further research. On the other hand, Ortiz García and Olaz Capitán (2021) pointed out that many people with disabilities think that starting up a business may be positively linked to their desire to not receive any more financial benefits from the government. In fact, many of their study participants indicated their desire to start their businesses in order to minimize their need for financial support from the government.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, this sociological perspective has not been widely used in entrepreneurship, so there is a dearth of interpretation on the topic of social entrepreneurship, hence, the relevance of this point of view is missing for varied minorities (Ortiz García & Olaz Capitán, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding individual capacities, it will be necessary to promote social skills in order to improve interpersonal relationships, in addition to reinforcing the skills needed to be able to lead an autonomous life. These improvements are achieved through programs that promote employability (e.g., , entrepreneurial competences (e.g., Barba-Sánchez et al, 2019Ortiz García and Olaz Capitán, 2021), learning (e.g., , or participation in artistic, cultural or recreational activities (e.g., Bosco et al, 2019). Regarding collective capacities, it will be necessary to consider issues related to equity (Ashton et al, 2020) and dignity (Aguado et al, 2015), and to sensitize society about social problems (Edwards et al, 2015).…”
Section: Social Accounting and Emotional Well-being In Disability Organizationsmentioning
confidence: 99%